Molecular screenings of drought tolerance QTLs and agronomic performance in selected rice (Oryza sativa) cultivars - SELVIA DEWI POHAN; HEPPY SETYA PRIMA; JAMSARI JAMSARI; TIKA RUNIFAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Pohan SD, Prima HS, Jamsari, Runifah T. 2025. Molecular screenings of drought tolerance QTLs and agronomic performance in selected rice (Oryza sativa) cultivars. Biodiversitas 26: 3731-3744. This study aimed to identify Quantitative Trait Loci (QTL) associated with drought tolerance (qDTY) and evaluate their agronomic performance under both non-stress and stress conditions. Molecular analysis using eight SSR markers (RM236, RM276, RM511, RM520, RM28099, RM28130, RM28166, and RM1261) was conducted to detect the presence of targeted qDTY loci. A Completely Randomized Design (CRD) with three replications was applied to assess the effects of drought stress on rice plants. Two treatments were implemented: a non-stress control (C1, 100% of field capacity) and a drought stress condition (C2, 50% of field capacity). Agronomic traits such as PH, PTN, PL, NFG, NUFG, DTF, and DTM were measured to evaluate plant performance under both conditions. The SSR markers used for detecting qDTY loci exhibited polymorphism. The number of alleles per marker averaged 8.625, ranging from 1 (RM511) to 12 (RM236). RM236 and RM28099 showed the highest polymorphism with eight alleles each. Phenotypic evaluation found significant differences in trait performance between non-stress and drought-stress conditions. While all traits generally decreased under drought stress (C2), the extent of reduction varied among genotypes. Most genotypes appeared to exhibit a drought escape mechanism by shortening their DTF and DTM under drought stress.